应用无量纲幅域参数诊断齿轮箱故障 - 王武秀; 沈玉娣 (Jixie chuandong)
this paper first discusses the functionalrelationship between dimensionless amplitude parameters and amplitude probability density of random signals then presents the results of computer simulationanalysis and experimental study of four states （for example normal, crack, pitting, fractue of gearbox,Meanwhile） the law governing the variation of dimen-tionless amplitude parameters with faults is expounded. A comparison of sensibilities and stabilities of parameters in the presence of practical signals is madethere fore the suitable diagnostic parameters is identified. On this basis, this paper defines kurtosis variation factor and makes trend analysis of the practicalsignals of gearbox, which will aid the surveillance andmaintenance of gearbox.